Error analysis of Arabic verbal system among the Malay learners in Malaysian universities - Ali, Asem Shehadeh Saleh (Mashreq International for Books Sdn Bhd, 2024)
This study attempts to investigate and analyze through Error Analysis the occurrences of linguistic errors among Malay students of Arabic in the use of the verbal system of Arabic. The Introduction highlights some issues and concepts pertinent to second/foreign language learning acquisition, as well as their implications to teaching. The objectives and importance of the study are discussed. The scope and limitation of this study, including an overview of the language situation and the teaching of Arabic in Malaysia are also touched upon. Chapter I present the verbal form of Arabic in a descriptive process. Chapter II analyzes through Error Analysis the identified errors committed by a group of Malay learners of Arabic. Interferences from the mother tongue are also analyzed. Chapter III traced the History of Teaching Arabic Language in Malaysia. Chapter IV analyzes the responses to the Questionnaire given to educators of Arabic Language at the International Islamic University Malaysia. The chapter is devoted to the problems of teaching Arabic at the University. The conclusion and recommendations are made based on the findings of this study with the aim of helping students in the learning of the target language. The pedagogical implications for the teaching of a second/foreign language are also discussed.